Maler, Bertil (2023): "El subdialecto gallego de Mondoñedo" (Edición e notas de Mariña Arbor Aldea e estudo bio-bibliográfico de Pär Larson). Monografía 14 da Revista Galega de Filoloxía. A Coruña: Universidade da Coruña. - Costas González, Xosé Henrique (Madrygal. Revista de Estudios Gallegos, 2023)
Review by Xosé Henrique Costas of El subdialecto gallego de Mondoñedo by Bertil Maler (edited and annotated by Mariña Arbor Aldea, with a bio-bibliographical study by Pär Larson), published as Monograph 14 of Revista Galega de Filoloxía (A Coruña, University of A Coruña, 2023).